2024
DOI: 10.1002/advs.202308031
|View full text |Cite
|
Sign up to set email alerts
|

YY1 Lactylation Aggravates Autoimmune Uveitis by Enhancing Microglial Functions via Inflammatory Genes

Jiaxing Huang,
Xiaotang Wang,
Na Li
et al.

Abstract: Activated microglia in the retina are essential for the development of autoimmune uveitis. Yin‐Yang 1 (YY1) is an important transcription factor that participates in multiple inflammatory and immune‐mediated diseases. Here, an increased YY1 lactylation in retinal microglia within in the experimental autoimmune uveitis (EAU) group is observed. YY1 lactylation contributed to boosting microglial activation and promoting their proliferation and migration abilities. Inhibition of lactylation suppressed microglial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Lactylation is a new method to transduce cellular metabolic characteristics into gene expression programs. Our studies and others have reported that lactylation can influence protein function and participate in multiple physiological and pathological processes [ 17 21 ]. The lactylation of H3K18 promotes the transcription of YTH N6-methyladenosine RNA-binding protein 2 (YTHDF2), which is involved in ocular melanoma [ 22 ].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Lactylation is a new method to transduce cellular metabolic characteristics into gene expression programs. Our studies and others have reported that lactylation can influence protein function and participate in multiple physiological and pathological processes [ 17 21 ]. The lactylation of H3K18 promotes the transcription of YTH N6-methyladenosine RNA-binding protein 2 (YTHDF2), which is involved in ocular melanoma [ 22 ].…”
Section: Introductionmentioning
confidence: 54%
“…As previous studies reported, histones play important roles in modulating chromatin structure and function, including transcriptional regulation [ 14 , 15 ]. Post-translational modifications could influence histone’s binding to the promoters of specific genes and then regulates gene transcription [ 20 , 21 ]. We found that hyperlactylation of H3K9 inhibited its interaction with HDAC2, and this process is reversed in response to glycolysis inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%